Kombinasi Logarithmic Percentage Change-Driven Objective Weighting dan Complex Proportional Assessment Dalam Penentuan Supplier Perlengkapan Olahraga - Pramuditya, Andri; Darwis, Dedi; Setiawansyah, Setiawansyah (Journal of Computer System and Informatics (JoSYC), 2024)
Sports equipment suppliers are suppliers that provide a wide range of equipment, clothing, and accessories needed by athletes, sports teams, and fans to support their activities. One of the main problems in choosing a sports equipment supplier is consistent product quality. Companies that choose sports equipment suppliers need to ensure that the products they buy meet the expected quality standards. In addition, the issue of stock availability and reliable delivery times is also a concern, as the inability to get goods on time can interfere with sports activities or businesses that depend on such equipment. The combination of Logarithmic Percentage Change-Driven Objective Weighting (LOPCOW) and Complex Proportional Assessment (COPRAS) provides a solid and adaptive framework for selecting sports equipment suppliers that best suit existing needs and priorities. This approach helps decision makers to make more informed and targeted decisions, taking into account the overall impact of each supplier's choice in the sporting goods industry. The results of supplier determination recommendations show the results of the assessment of each supplier, based on calculations using a combination of LOPCOW and COPRAS for the first rank with a utility value of 100 obtained by TRB Suppliers. The results of applying the combination of LOPCOW and COPRAS methods in supplier determination can provide more holistic and accurate results, the combination of these two methods can provide a more complete and detailed view of optimal supplier selection, taking into account dynamic changes in relevant criteria and preferences.